Does the Presence or a High Titer of Yellow Fever Virus Antibodies Interfere with Pregnancy Outcomes in Women with Zika Virus Infection? - Isa Cristina Ribeiro Piauilino; Raillon Keven dos Santos Souza; Maurício Teixeira Lima; Yanka Karolinna Batista Rodrigues; Luís Felipe Alho da Silva; Ayrton Sena Gouveia; Alexandre Vilhena da Silva Neto; Bárbara Aparecida Chaves; Maria das Graças Costa Alecrim; Camila Helena Aguiar Bôtto de Menezes; Márcia da Costa Castilho; Djane Clarys Baia-da-Silva; et al. (Viruses, 2023)
Zika virus (ZIKV) and yellow fever virus (YFV) originated in Africa and expanded to the Americas, where both are co-circulated. It is hypothesized that in areas of high circulation and vaccination coverage against YFV, children of pregnant women have a lower risk of microcephaly. We evaluated the presence and titers of antibodies and outcomes in women who had ZIKV infection during pregnancy. Pregnancy outcomes were classified as severe, moderate, and without any important outcome. An outcome was defined as severe if miscarriage, stillbirth, or microcephaly occurred, and moderate if low birth weight and/or preterm delivery occurred. If none of these events were identified, the pregnancy was defined as having no adverse effects. A sample of 172 pregnant women with an acute ZIKV infection confirmed during pregnancy were collected throughout 2016. About 89% (150 of 169) of them presented immunity against YFV, including 100% (09 of 09) of those who had severe outcomes, 84% (16 of 19) of those who had moderate outcomes, and 89% (125 of 141) of those who had non-outcomes. There was no difference between groups regarding the presence of anti-YFV antibodies (p = 0.65) and YFV titers (p = 0.6). We were unable to demonstrate a protective association between the presence or titers of YFV antibodies and protection against serious adverse outcomes from exposure to ZIKV in utero.